عزل بعض الفطريات الدعامية Basidiomycetes ودراسة تأثير أوساط مغذية مختلفة في نموها الإعاشي ( في الزجاج ) - يازجي ميساء (Latakia University Journal -Biological Sciences Series, 2019)
اختبرت قدرة ثلاثة عشر نوعاً من الفطريات الدعامية هي:Lepista nuda, Omphaletus olearius, Tricholoma terreum, Tscalpturatum, Coprinus micaceus, Armillaria mellea, Pleurotus ostreatus, Amanita ovoidea, Volvaria gloiocephala, Russula paludosa, Lactarius deliciosus, Boletus granulatus, B.luridus على النمو الإعاشي وتشكيل المشائج، وذلك بزراعة نسيج القبعة وأبواغ هذه الفطريات، في الزجاج، على أربعة أوساط مغذية مختلفة هي: خلاصة البطاطا (P.D.A)، خلاصة الشعير (M.EA)، Lima bean وSabouraud. أظهرت النتائج قدرة تسعة أنواع منها على النمو وإعطاء مشائج اختلفت بصفاتها الفيزيولوجية وبسرعة نموها، وذلك باختلاف الوسط المغذي أو الجزء المزروع من الفطر، كما اختلفت المتطلبات الغذائية لهذه الأنواع. كان الوسطانP.D.A وM.E.A أكثر ملاءمة لتشكيل مشائج كثيفة، سريعة النمو مقارنة مع مشائج الأنواع النامية على الأوساط الأخرى وتميّز النوع Omphaletus olearius بأنه أعطى نمواً كاملاً على الأوساط M.E.A، P.D.A و Sabouraud بعد 15، 17 و20 يوماً على التوالي، في حين أعطى النــوعLepista nuda نمواً كاملاً فقط على الوسط Lima bean بعد 5 أسابيع من بدء النمو، وذلك اعتباراً من الزراعات النسيجية، أما النوع Boletus granulatus فقد أعطى نموا كاملاً فقط على الوسط P.D.A بعد 4 أسابيع اعتباراً من الزراعات البوغية. بيّنت النتائج إمكانية النمو الإعاشي وتشكيل مشائج من بعض أنواع الدعاميات على الوسط Sabouraud. The capacity of thirteen species of Basidiomycetes: Lepista nuda, Omphaletus olearius, Tricholoma terreum, T.scalpturatum, Coprinus micaceus, Armillaria mellea, Pleurotus ostreatus, Amanita ovoidea, Volvaria gloiocephala, Russula paludosa, Lactarius deliciosus, Boletus granulatus, B.luridus on the vegetative growth and formation of mycelia are tested by the, in vitro, culture of pileus tissue and spores of these fungi on four different nutritive media: Potato extract (P.D.A), Malt extract (M.E.A), Lima bean and Sabouraud. The results demonstrated the capacity of nine species on the growth and production of mycelia were different from their physiologic characters and growth rate, depending on the nutritive media or the planted fragment of the fungi, and the nutritive requirement for these species were differ. The two media, M.E.A and P.D.A, were the most suitable for the formation of mycelia dense and fast growth in comparison with the mycelia of species are growing on the other media. The species Omphaletus olearius giving complete growth on M.E.A, P.D.A and sabouraud media after 15, 17, 20 days respectively. While the species Lepista nuda gave complete growth only on Lima bean medium after 5 weeks of tissue culture, whereas the species Boletus granulatus gave complete growth only on P.D.A medium after 4 weeks of spores culture. The results indicated that the vegetative growth and formation of mycelia from some Basidiomycetes is possible on Sabouraud medium.